Speech Denoising Using Mixed Transform - Abou-loukh, Sadiq J.; Ibrahim, Ali K. (Nahrain University College of Engineering Journal, 2017)
This paper presents a mixed transformbased speech denoising technique obtained by thecombination of multicircularlet and slantlettransforms and thresholding algorithm. It is wellknown that denoising is a compromise between theremoval of the largest possible amount of noise andthe preservation of signal integrity. Mixedtransform is an intelligent tool for solving speechprocessing problems such as speech denoising , thegeneral algorithm of speech denoising usingdiscrete wavelet transform (DWT) is presented,followed by the proposed general algorithm ofspeech denoising using mixed transform. Thispaper also discusses the effect of using DWT andmixed transform in speech denoising,theirperformances in terms of mean square error(MSE) and peak signal to noise ratio (PSNR) areassessed. Computer simulation results indicate thatthe mixed transform offers better MSE and PSNRthan DWT.